MENINGKATKAN HASIL BELAJAR MEMBACA LEGENDA MELALUI MODEL NUMBERED HEADS TOGETHER SISWA SMPN 8 SURAKARTA - Sri Suprapti (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2017)
The purpose of this study to enhance the activity and achievement in the Javanese language for the reading material of legend using cooperative learning methods Numbered Heads Together (NHT). This study used a two-cycle classroom action research. Subjects in this study were 32 students of class VIII E SMPN 8 Surakarta in the 2015/2016 school year, consisiting of 18 girls and 14 boys. The research was conducted in two cycles. Each cycle has four phases: planning, implementation, observation and reflection. In the first cycle the researcher used NHT without media and in Cycle II,  NHT was used with instructional media. Results of the study showed increased percentage of the motivation to learn the Javanese language to read the Legend. Description of the achievement included: listening and attention to the teacher's explanations was 34.38%; encouragement to ask and express opinions was 31.25%; and the ecouragement to present results of group discussions in class was 59.38%.l